2005
DOI: 10.1103/physrevb.72.144504
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and physical properties ofBa24Si100determined from electric transport, specific-heat capacity, and magnetic susceptibility measurements

Abstract: Both Ba 24 Si 100 and Ba 24 Ge 100 with crystallographically identical structure are found to be superconducting at 1.4 and 0.27 K, respectively. Physical properties of this superconductor Ba 24 Si 100 are studied by electric transport, specific heat capacity, and magnetic susceptibility measurements. The density of states at the Fermi level N E F = 0.148 states eV −1 ͑Si atom͒ −1 and a distinct jump of C p at the superconducting transition temperature ⌬C p = 0.272 J K −1 mol −1 are obtained. An exponential fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Fig. 6 showed the density maps of these three kinds of Ba atoms at 100 K [15]. Immediately we can recognize that the Ba(3) accommodated in the open cage structure rattles in a very anisotropic fashion, while Ba (1) and Ba(2) atoms do isotropically in the case of the Ge 100 network.…”
Section: Superconductivity In Si 100 and Ge 100 Network: Rattling Phmentioning
confidence: 92%
“…Fig. 6 showed the density maps of these three kinds of Ba atoms at 100 K [15]. Immediately we can recognize that the Ba(3) accommodated in the open cage structure rattles in a very anisotropic fashion, while Ba (1) and Ba(2) atoms do isotropically in the case of the Ge 100 network.…”
Section: Superconductivity In Si 100 and Ge 100 Network: Rattling Phmentioning
confidence: 92%
“…Two types of Ba-intercalated pure silicon network solids showing superconductivity have been now reported, one being Ba 8 Si 46 [1,2] and the other Ba 24 Si 100 [3]. Historically, Ba 24 Si 100 was reported to be synthesized under high pressure [4], but it seemed not to show superconductivity.…”
Section: Introductionmentioning
confidence: 97%
“…Historically, Ba 24 Si 100 was reported to be synthesized under high pressure [4], but it seemed not to show superconductivity. However, our recent soft X ray studies showed that the density of states at the Fermi level is sufficiently large and superconductivity has been searched for a high quality sample, ending up in a new finding of superconductivity [3]. It is also interesting that the type II Si 136 does not superconduct even when Ba is introduced as intercalants [5].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The superconductivity in Ba 24 Ge 100 sharply rises from T C ¼ 0:24 K to 3.8 K under a pressure of 2.8 GPa [6]. It is very interesting that the crystallographically identical Ba 24 Si 100 early synthesized by Yamanaka et al in 2000 [7] was found to be superconducting later in 2005, and the temperature evolution of superconductivity shows an opposite behavior to that of Ba 24 Ge 100 [8].…”
mentioning
confidence: 98%